Physical and chemical attributes of a soil cultivated with rubber tree under three management strategies - dos Santos, Yuri Luiz Augusto; Ribon, Adriana Aparecida; Caixeta Bitencourt, Luis Filipe; Barros, Leonardo Rodrigues; Fernandes, Kathleen [UNESP]; Correchel, Vladia; Leandro, Wilson Mozena; Backes, Clarice; Marques Santos, Alessandro José; Giongo, Pedro Rogério (Universidade Estadual de Londrina, 2020)
Rubber tree (Hevea brasiliensis) is a native species of the Amazon biome. This species had great economic importance due to the production of latex, used to obtain natural rubber. Seeking growth in productivity with adequate management is necessary to optimize production and increase areas with rubber trees. This study aimed to verify the physical and chemical attributes of soil under three different managements and two rubber tree clones, searching for the best alternative for the general edaphoclimatic conditions of the Cerrado biome. The experiment was installed in Palmeiras of Goiás, GO, Brazil, in a randomized block design in a 2×3 factorial arrangement, consisting of two rubber tree clones (PB 312 and RRIM 600) and three management strategies (organomineral fertilizer with poultry litter, pigeon pea as green manure, and mechanical mowing-brushcutter). Physical attributes such as soil density, soil penetration resistance, soil moisture and aggregation, soil fertility, and tree development were analyzed. Statistical analyses of variance and Tukey test were carried out in order to compare the dendrometric data and physical and chemical attributes of the soil under the different treatments applied in the inter-row of rubber trees. No significant statistical differences were found among treatments and between clones in relation to soil physical attributes. However, the soil pH reduced the use of organomineral fertilizer and the clone RRIM 600 had the highest heights.
Atributos físicos e químicos de um solo cultivado com seringueira sob três sistemas de manejo
Keywords: Fertility; Hevea brasiliensis; Organomineral fertilizer; Red Latosol; Rubber cultivation